Intramuscular spindle cell lipoma/pleomorphic lipoma unusual site fore arm - Jacob, Anu Anna; N., Geethanjali; Poothiode, Usha (International Journal of Research in Medical Sciences, 2018)
Pleomorphic lipoma/ spindle cell lipoma accounts for 15 % of lipoma within extremities, confining to the superficial plain comprising lower dermis and subcutaneous tissue. Intramuscular presentation in extrimities is a rare presentation. Here is a case of deep seated pleomorphic lipoma, of forearm, both on fine needle aspiration, biopsy and IHC confirmation. 100% of benign cases of lipoma are positive for CD 34, as stated in many studies and was also positive in our case.